Pose estimation and map building with a Time-Of-Flight-camera for robot navigation. (20th November 2008) - Prusak, A.; Melnychuk, O.; Roth, H.; Schiller, I.; , R. Koch
In this paper, we describe a joint approach for robot navigation with collision avoidance, pose estimation and map building with a 2.5D Photonic Mixer Device (PMD)-camera combined with a high-resolution spherical camera. The cameras are mounted at the front of the robot with a certain inclination angle. The navigation and map building consists of two steps: when entering new terrain the robot first scans the surrounding. Simultaneously a 3D-panorama is generated from the PMD-images. In the second step, the robot moves along the pre-defined path, using the PMD-camera for collision avoidance and a combined Structure-from-Motion (SfM) and model-tracking approach for self-localisation. The computed poses of the robot are simultaneously used for map building with new measurements from the PMD-camera.